An Analysis of The Application of The Arcs Model in Physics Learning: A Systematic Review of Studies from 2016-2024 - Kafa Pramitha Anggraini Indhira Artanti; Sentot Kusairi; Nasikhudin Nasikhudin; Yustina Safitri; Monika Ruth Cahayana; Ivan Danar Aditya Irawan; Khoirun Nisa’ (Jurnal Ilmiah Pendidikan Fisika, 2025)
This study investigates the development, implementation, and impact of the Attention, Relevance, Confidence, Satisfaction (ARCS) model in physics education. A Systematic Literature Review (SLR) using the PRISMA approach was conducted by analyzing relevant studies published between 2016 and 2024. From an initial search of 687 articles, 9 studies indexed in SINTA and Scopus met the inclusion criteria and were analyzed. This study found that research on the ARCS model in physics education shows a consistent publication trend, dominated by studies at the high school level and focused on basic physics topics such as kinematics, heat, and magnetism. The ARCS model was applied both independently and in combination with modern approaches, including flipped classrooms, e-learning, and mobile learning. The findings indicate that the ARCS model effectively enhances student motivation, learning outcomes, and conceptual understanding, demonstrating its strong pedagogical adaptability across learning contexts. However, most studies emphasize general motivation rather than higher-order outcomes. This study concludes that the ARCS model has significant potential as a flexible motivational framework in physics education, highlighting the need for future research on its effectiveness in promoting critical thinking, creativity, and concept mastery in more complex physics topics.